Main historical tendencies of the process of training of figures in the artistic swimming (Review) (Revista científica Olimpia, 2021)
In this article a bibliographic and documentary review has been made in which it is intended to delve into the main historical trends in the training process of figures in artistic swimming. In this way we will know its genesis and milestones that frame the development of the training and competition of the figures.
Keywords: figures in artistic swimming; training; history